Identification of the intonation of verbal inducements - Elijošiūtė , S. (Psichologija, 1971)
Experimental research of the intonations of verbal inducements in the Russian language has been carried out. The perception level in the process of communication has been studied. 106 auditors gave 4898 answers which made it possible to maintain that the intonations of verbal inducements are identified as belonging to certain zones of intonations. The verbal inducements under investigation fell into three zones having the communicative meanings of necessity, desirability and possibility of action fulfilment.